PENGARUH MODERNISASI TERHADAP PRAKTIK MAHAR DALAM MASYARAKAT - Muhammad Khalil; Aten Kuswendi; Susi Kusmawaningsih (Syariah: Jurnal Hukum Keluarga Islam, 2025)
Mahr is something that must be given by the husband to the wife in marriage, according to the view of the majority of scholars. Mahr is not a form of buying and selling, but a symbol of respect, love, and the husband’s commitment to his wife. Giving mahr is one of the obligations in marriage that holds significant meaning in the relationship between husband and wife. Although the Qur’an does not explicitly mention a specific amount for the mahr, it clarifies that mahr should be given in a good manner and according to the husband’s ability. Therefore, the amount of mahr can vary depending on the circumstances of each couple and the existing cultural practices. This article examines how modernization has influenced dowry practices in various societies around the world. Dowry, as a gift from men to women during the marriage process, has experienced significant changes due to developments in technology, economics, education, as well as socio-cultural changes that have come with modernization. Through a literature review of various empirical studies in various parts of the world, this article identifies changes in the form, value, meaning and function of dowry in contemporary society. The results of the study show that modernization has produced dowry practices that are more diverse, dynamic and contextual, although this does not always eliminate its cultural essence. Understanding changes in dowry practices is important to obtain a more comprehensive picture of the transformation of the institution of marriage and gender relations in modern society.